Urokinase-type plasminogen activator deficiency enhances CD8+ T cell infiltration and anti-PD-1 therapy efficacy in prostate cancer - Li, Xiaoyi; Zhang, Xiao; Fu, Xing; Wu, Hong; Ye, Xinyu; Huang, Xin; Cui, Yuhao; Qian, Chao-Nan; Lu, Yi; Zhang, Jian (Frontiers in Immunology, 2025)
IntroductionUrokinase-type plasminogen activator (uPA) is upregulated in prostate cancer, but its comprehensive impact on the immune microenvironment and the underlying mechanisms remains to be fully elucidated.MethodsuPA expression was analyzed in clinical prostate cancer specimens and correlated with CD8⁺ T cell infiltration. Tumor growth was assessed in the uPA-deficient (uPA–/–)and the uPA inhibitor UK122-treated mouse model. Immune infiltration was evaluated by CyTOF and flow cytometry. Anti-CD19 chimeric antigen receptor (CAR)-engineered WT or uPA–/– CD8⁺ T cells were tested for cytotoxicity against RM1-CD19 cells. The combination of UK122 and anti-PD-1 therapy was assessed.ResultsElevated uPA in prostate cancer specimens inversely correlated with CD8⁺ T cell infiltration. Both genetic uPA ablation and UK122 significantly attenuated tumor growth by enhancing antitumor immunity. uPA deficiency markedly increased CD8⁺ T cell infiltration. uPA–/– CD8⁺ T cells exhibited enhanced cytotoxicity compared to WT CD8⁺ T cells. Tumor-infiltrating uPA–/– CD8⁺ T cells showed higher PD-1 expression. UK122 synergized with anti-PD-1 therapy to promote tumor regression.DiscussionuPA is a significant immunosuppressive regulator in prostate cancer. Its inhibition enhances CD8⁺ T cell function and synergizes with immune checkpoint blockade, supporting uPA targeting as a novel strategy to improve prostate cancer immunotherapy efficacy.